Thrombosis of the dorsal vein of the penis as first clinical presentation of pancreatic cancer metastatic to the penis. Issue 6 (December 2019) - Virdis, Matteo; Bonifacio, Cristiana; Brambilla, Tatiana; Capretti, Giovanni; De Nittis, Pasquale; Uccelli, Fara; Zerbi, Alessandro
Introduction: Though metastatic disease is a common presentation of pancreatic adenocarcinoma, localization to the penis is an extremely rare event despite its abundant vascularization. Primary cancers responsible for penile metastases usually occur in prostate and rectum and are often associated with disseminated malignancy and poor prognosis. Case description: A 66-year-old man was diagnosed with adenocarcinoma of the tail of the pancreas after the onset of thrombosis of the dorsal vein of the penis; pubis ultrasound and total body computed tomography scan were negative for metastases at other sites. The patient was submitted to distal pancreatectomy with splenectomy for a pT3 N1 G4 pancreatic ductal adenocarcinoma. Three weeks after discharge, the patient returned to the outpatient clinic complaining of a painful permanent turgidity of the penis shaft. Ultrasound revealed a complete replacement of the cavernosal bodies by multiple nodular masses and a penile biopsy confirmed metastases from the primary pancreatic cancer. The patient started chemotherapy with NAB-paclitaxel and gemcitabine, with excellent control of symptoms. However, the disease progressed to bone and liver and the patient died 9 months after surgery. Conclusions: Penile localization is an extremely rare event and a standard of care has not been elaborated. Treatments are palliative and mainly aimed at pain relief and can comprise chemotherapy, radiotherapy, and surgery. Identification of venous thrombosis as an early sign of involvement could potentially offer patients an earlier diagnosis and a better treatment option.